Apatite textural and geochemical insights into the petrogenesis of intrusive rocks - Haina Li; Jun Han; Fengli Li; Heyang Li; Zhonghai Zhao; Yang Liu; Jiayu Chen; Yechang Yin; Yu Han (Scientific Reports)
Abstract Apatite is widely used as an indicator mineral to reflect the characteristics and petrogenesis of host magma. In this study, we present apatite geochemical and in-situ Sr–Nd isotopic data of monzogranite, granodiorite and dioritic enclave in the eastern Songnen-Zhangguangcai Range Massif, aiming to fingerprinting their petrogenesis and magmatic evolution processes. Based on apatite textures and geochemistry characteristics, the apatites were categorized into two distinct groups. Group 1 apatites have subhedral-anhedral textures and high Sr content (> 500 ppm). The majority of their εNd(t) values are relatively consistent with those of host monzogranites, indicating that they crystallized from crustal-derived material. Conversely, Group 2 magmatic apatites have euhedral-subhedral and core-rim textures, as well as low Sr content (< 500 ppm). This group can further be divided into two subgroups of Group 2A and 2B based on zoned textures and compositions. Group 2A zoned apatites exhibit high Sr/Nd and Sr/Y ratios at the rim and have discontinuous Ba contents, suggesting that they were derived from magma mixing and the granodiorite may be the felsic end-member. The Group 2B apatites are characterized by high Ce and Eu contents with low Y contents and Sm/Nd ratios, indicating that they originated from metaluminous I-type granitoids. The apatites also record the magmatic evolution processes, including fractional crystallization of plagioclase and titanite, as well as fluid exsolution. Combining apatite and whole rock geochemistry, it is shown that the parental magma was related to subduction of Mudanjiang Oceanic crust.